2007
DOI: 10.1088/0967-3334/28/8/004
|View full text |Cite
|
Sign up to set email alerts
|

Arterial pulse waveform analysis by the probability distribution of amplitude

Abstract: Augmentation index (AIx) calculated from the pressure waveform of an artery is widely used to quantify the arterial stiffness and evaluate the cardiovascular risk. The key for calculating AIx is to locate the inflection point on the waveform signal, which is caused by the wave reflection. This study applies the probability distribution of the pressure waveform to identify the inflection point for estimating AIx. The results show that the pulse wave probability analysis not only can estimate AIx with a better t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This study showed that TDB is a robust and stable parameter representing arterial stiffness from PPG measurement. Statistical parameters can also be used for estimating the augmentation index from the PPG signal (Tsui et al 2007). However, it is not real-time processing and therefore is not suitable for continuous real-time blood pressure monitoring.…”
Section: Waveform Analysis Of Ppgmentioning
confidence: 99%
“…This study showed that TDB is a robust and stable parameter representing arterial stiffness from PPG measurement. Statistical parameters can also be used for estimating the augmentation index from the PPG signal (Tsui et al 2007). However, it is not real-time processing and therefore is not suitable for continuous real-time blood pressure monitoring.…”
Section: Waveform Analysis Of Ppgmentioning
confidence: 99%
“…The working principle of this algorithm was described by other authors (Tsui et al, 2007), relies on the PDF property of creating a local maximum for the amplitudes close to the inflection point that defines AIx.…”
Section: Probability Density Functionmentioning
confidence: 99%
“…Therefore, quantitative methods are needed. Much effort is being spent on pulse analysis, such as the classification of pulse waveforms [1][2][3][4][5][6][7] and cardiovascular assistant diagnosis [8][9][10][11]. In pulse diagnosis, time-domain parameters can reflect the specificity of pulse signals.…”
Section: Introductionmentioning
confidence: 99%